ANALISA PENERAPAN PAPERLESS OFFICE PADA PROSES IN ROOM CHECK IN OLEH GUEST RELATION OFFICER PADA HOTEL SHANGRI-LA SURABAYA - Risalah, Fitria Amaliatur; Faozen, Faozen (Sadar Wisata: Jurnal Pariwisata, 2019)
Abstrakâ€œThe Analysis of Paperless Office Implementation for In Room Check In Process by Guest Relation Officer at Shangri La Hotel Surabayaâ€ is a research that focused to answer the questions about the paperless office implementation for in room check in, the operational in front office department, and duties and responsibilities of guest relation officer which are applied in Shangri La Hotel Surabaya. In order to understand the implementation of paperless office for in room check in, duties and responsibilities of guest relation officer and the operational in front office department. This is a qualitative descriptive research which is using descriptive analysis and SWOT matrix. The methods of collecting data that used in this research are literatures, questionnaires, observation and documentation which then analyzed by descriptive analysis, IFE and EFE matrix, IE matrix, and SWOT matrix. The result of this research was found that implementation of paperless office was working well and the implementation for in room check in was also working well even there are several problems. But the problems were already fixed by management, staff, and the trainees. One of problems is when the registration card cannot be uploaded and it is suddenly disappear. The solution is the staffs or trainees should capture it with screen capture feature on surface pro, so the registration card can be uploaded manually. Besides that, there are also found strengths, weaknesses, opportunities, and threats (SWOT) of paperless office implementation and in room check in that arranged in SWOT matrix.